Antioxidant, Anti‐inflammatory and Cytotoxic Activities of Polyphenols Extracted from Chroogomphus rutilus. Issue 1 (9th December 2019) - Zhang, Ye; Lan, Meng; Lü, Jin‐Peng; Li, Jing‐Feng; Zhang, Kai‐Yue; Zhi, Hui; Zhang, Hui; Sun, Jia‐Ming
Abstract: Chroogomphus rutilus is a rare fungal species that grows under pine trees and is now widely used as a functional food and pharmaceutical product. However, the chemical constituents and biological activities of Chroogomphus rutilus have been relatively limited. The present study aimed at determining the total polyphenols and flavonoids contents, biological activities and main phenolic compounds of Chroogomphus rutilus from different geographical origins at the stipe and pileus. The results suggested that Chroogomphus rutilus polyphenol extracts revealed a higher antioxidant, anti‐inflammatory, and cytotoxic activities, and there were significant differences between samples from different locations and regions. Correlation analysis showed that the contents of total polyphenols and flavonoids were significantly correlated with antioxidant and anti‐inflammatory activities. However, only the content of total flavonoids was significantly correlated with cytotoxicity, which means that the cytotoxicity of Chroogomphus rutilus polyphenol extracts may be regulated by flavonoids or other compounds. HPLC‐DAD analysis revealed that the main phenolic compound was protocatechuic acid, followed by baicalin, p ‐hydroxyphenylacetic acid and p ‐hydroxybenzoic acid, but comparing with the pileus extracts, the stipe extracts can be considered as a higher concentration of phenolic compounds. Therefore, antioxidant, anti‐inflammatory and cytotoxic activities of Chroogomphus rutilus polyphenol extracts could be due to the identified compounds. This study investigated a deep knowledge about the constituents and activities of Chroogomphus rutilus and provided the reference for its application in food and pharmaceutical. Abstract :